Analisis Pengaturan Status Kewarganegaraan Seseorang Yang Melakukan Perkawinan Campuran Di Indonesia Dari Perspektif HAM - I Made Lanang Maha Adi Putra; Ni Made Ari Yuliartini Griadhi (Universitas Katolik Widya Karya Malang, 2023)
This study aims to find out and understand the regulation of the citizenship status of a person who enters into mixed marriages in Indonesia, and to know and understand this regulation from a human rights perspective. The method used is normative research using a conceptual approach and a statutory approach. The results of the research show that the provisions of Article 26 of Law no. 12 of 2006 concerning Citizenship basically provides for restrictions on human rights related to a person's freedom to choose citizenship status. These provisions stipulate that as a result of mixed marriages, Indonesian men or women lose their citizenship status because according to the law of origin the foreign husband or wife has given citizenship status. In addition, this provision also contradicts Article 28E paragraph (1) of the 1945 Constitution of the Republic of Indonesia which basically states that everyone is free to embrace religion and worship according to their religion, choose education and teaching, choose a job, choose citizenship, choose a place to live in the territory of the country and leave it. and has the right to return. and also Article 26 paragraph (1) of Law no. 39 of 1999 concerning Human Rights which basically states that everyone is given the right to own, replace, obtain or maintain citizenship status.